Cost Analysis of Additional Rainfall Station in The Kayan River Area, North Kalimantan Province - Fadzil Abdillah; Hanie Teki Tjendani; Esti Wulandari (Enrichment: Journal of Multidisciplinary Research and Development, 2026)
With a total area of the Kayan River Basin (WS) reaching 3,178,215.72 hectares, when compared to other River Basins in Kalimantan, the Kayan WS only has seven rain gauge stations, of which six are in good condition and one is damaged or inactive. Therefore, it is important to determine the appropriate rationalization method in order to obtain the appropriate number and distribution of rain gauge stations and can represent the characteristics of the area in the Kayan River Basin. The method used to analyze the rationalization of these rain gauge stations includes determining the maximum need, minimum need, and the Kagan-Rodda method. After evaluating several methods, the most suitable method for rationalizing rain stations in the Kayan WS is the Kagan-Rodda method. The results of the evaluation of the need for rain stations in the Kayan River Basin are 33 (thirty-three) stations, the existing rain stations are 6 (six) stations, the need for the addition of 27 (twenty-seven) new rain stations.